Red thread thinking : weaving together connections for brillant ideas and profitable innovation - Kaye, Debra (McGraw Hill-Ascent Audio, 2013)
Create products and services your consumers can't pass up--without the high cost of development Debra Kaye explodes conventional thinking about innovation and provides an approach that anyone or any business can use to expose the crucial links among observations, experiences, facts, and feelings that on the surface do not seem related--but are--to uncover fresh, brilliant insights. In Red Thread Thinking, Kaye shows you how to weave originality from disparate information and turn it into a product or service that can shake up the marketplace--and your business. A mold-breaking system, Red Thread Thinking sharpens your innovation skills and can assist in problem solving, whether preparing a talk, pitching a project to your colleagues and boss, managing staff in a more productive way, or taking business to a new level. Learn the ways of Red Thread Thinking: Red Thread One: "Innovation--It's All in Your Head"--We can fire up our brains to become better at observing and interpreting what we see around us Red Thread Two: "Everything Old is New"--Take a fresh look at the past to gain remarkable advantage Red Thread Three: "People: The Strangest Animals in the Zoo"--Know what makes your market tick, and you'll know what makes them spend Red Thread Four: "What You See Is What You Get"--Learn how to create an entirely new and accessible "language" to make your product stand out and be universally understood Red Thread Five: "The Force of Passion"--Persevere, review, and refine your ideas without compromising your integrity or core beliefs. Red Thread Thinking teaches you to activate your own knowledge and resources to make better connections, have more and superior insights, and apply history as a valuable source for future-leaning innovation. Praise for Red Thread Thinking "A must read for entrepreneurs hoping to take their ideas from fuzzy to firm."--Susan Cain, New York Times bestselling author of Quiet: The Power of Introverts in a World That Can't Stop Talking "Red Thread Thinking provides a deliberate system to create a 'revolution in your mind'--the first order of business for any innovator who wants to shift the consumer landscape and offer value and usefulness to customers." -- Jay Walker, Chairman, Walker Digital; founder of Priceline.com "A fascinating read that should hearten anyone who wants to apply proven strategies to the act of collecting and connecting dots that exist for us all--if only we'd stop and notice." -- Danny Meyer, New York Times bestselling author of Setting the Table: The Transforming Power of Hospitality in Business "In Red Thread Thinking, Debra Kaye offers a framework for innovation that embraces--indeed harnesses--the power of serendipity, free association, and our mind's elastic ability to see what's new in the familiar." -- Jean-Marie Dru, Chairman, TBWA\Worldwide "Debra Kaye has created an approach to innovation that combines simple, pragmatic steps on the journey of innovation to benefit any serious entrepreneur or manager who believes innovation is central to business and that it is not the mysterious privilege of a few." -- Thomas Pinnau, Chief Executive Officer, Knowledge Universe Work-Life Solutions